Unstable instantons in A-model localization - Emil Hakan Leeb-Lundberg (Journal of High Energy Physics)
Abstract We apply localization techniques to A-twisted N $$ \mathcal{N} $$ = (2) theories of vector multiplets on S 2. We derive formulae for A-model partition functions and correlators as integrals along a real contour, as opposed to a complex one. Using the correlator formula, we successfully recover the unstable instanton partition function of pure two-dimensional Yang-Mills theory from the vacuum expectation value of an A-model operator.